A Genealogical Analysis on the Concept and Development of Maqaṣid Syarī‘ah - Nur, Iffatin; Abdul Wakhid, Ali; Handayani, Lestari (Universitas Islam Negeri Raden Intan Lampung, 2020)
Maqāṣid syarī‘ah has a tremendous urgency to the process of Islamic law’s adaptability and modernization, especially in response to the increasingly complicated and crucial human problems where the treasures of classical fiqh are no longer capable to answer them. This paper studies a genealogical analysis to answer the question about the origin of the concept of maqāṣid syarī‘ah by uncovering its embryo and genes of this completely new concept. It was library research employing discourse analysis. Primary and secondary sources of works from previous and contemporary Muslim scholars discussing maqāṣid were studied and analyzed using Gadamer’s hermeneutics. The study found that from the historical perspective, maqāṣid syarī‘ah did not just emerge at the time of al-Syaṭibi, but, based on empirical data, it had been present long before his time. The literature analysis on uṣūl fiqh concluded that the figures before al-Syaṭibi had developed some works that were actually in the area of the essential and substantial values of maqāṣid syarī‘ah, however, they presented them using other words and terms so that they were considered as not of maqāṣid syarī‘ah.